Effect of glycerol on properties of chitosan/chlorhexidine membranes and antibacterial activity against Streptococcus mutans - Hachity-Ortega, José Alberto; Jerezano-Domínguez, Alberto V.; Pazos-Rojas, Laura Abisai; Flores-Ledesma, Abigailt; Pazos-Guarneros, Diana del C.; Parra-Solar, Karla Aimée; Reyes-Cervantes, Eric; Juárez-Díaz, Ismael; Medina, Manuel E.; González-Martínez, Mayra; Castillo-Silva, Brenda Eréndida; Ávila-Curiel, Beatriz Xochitl; et al. (Frontiers in Microbiology, 2024)
Chitosan membranes with glycerol can function as an effective dispersing agent for different antibiotics or active ingredients that can be used in the treatment of diseases present in the oral cavity. The effects of the addition of glycerol on the mechanical, water absorption, swelling, pH, thickness, disintegration, rugosity, and antibacterial properties of chitosan-chlorhexidine-glycerol membranes were investigated in this study. Mechanical results indicated that chitosan membranes' rugosity, strength, flexion, and thickness differed at loading 1, 3, 5, 10, 15, and 20 % of glycerol (p < 0.05). The chitosan membranes' rugosity, dissolution, strength, and pH results were significantly enhanced by the presence of glycerol at 3, 5, and 10% concentrations. In this investigation, the antimicrobial activity model used was the inhibition of Streptococcus mutans CDBB-B-1455 by chitosan-chlorhexidine membranes. It was observed that there was no change in inhibition with different concentrations of glycerol. The results suggest that chitosan-glycerol-chlorhexidine membranes may be a potential candidate for topical antiseptic application in buccal-dental disorders caused by S. mutans, such as caries, periodontal diseases, and oral squamous cell carcinoma, helping to prevent the development of serious conditions that can compromise human health.